Evaluation of microleakage in composite restorations after several aging periods - Carla Grimaneza Molina-Pule; Iván Ricardo García-Merino; Jonathan Eduardo Aldas-Ramírez; Gabriela Marina Falconí-Borja; Ana del Carmen Armas-Vega (Universidad de Antioquia, 2015)
Introduction: currently, resin composites are the materials of most frequent use in dentistry. The purpose of this study was to evaluate the level of microleakage in direct composite restorations. Methods: 60 recently extracted third molars were collected and sorted out into three groups. Two cavities were prepared on each tooth, one in the buccal surface and one in the lingual surface. The same composite (Vococid Gel, Admira Bond and admires A2 - Voco) was used to perform the restorations of all the cavities, closely following the manufacturer's recommendations. The samples were sorted out into three groups (n= 20) according to different thermocycling times. Group 1: 5,400 cycles during 6 months; Group 2: 8,100 cycles during 9 months; Group 3: 10,800 cycles during 12 months, at a temperature of 5, 37, and 55°C respectively. The entire surface of each sample was isolated with the exception of 2 mm around the restoration, and then they were pigmented with methylene blue for 24 hours. Next, each sample was longitudinally cut in order to evaluate the degree of microleakage. Results: the collected data were subjected to ANOVA, Tukey, and Student's t-test, finding out p<0.05, which suggests that there is no significant difference among the thermocycling times. Conclusion: the results show that the restorative material under evaluation has dimensional stability 6, 9, and 12 months after application.